The nature of consciousness - Rowlands, Mark (Cambridge University Press, 2001)
In The Nature of Consciousness, Mark Rowlands develops an innovative account of the nature of phenomenal consciousness, one that has significant consequences for attempts to find a place for it in the natural order. The most significant feature of consciousness is its dual nature: consciousness can be both the directing of awareness and that upon which awareness is directed. Rowlands offers a clear and philosophically insightful discussion of the main positions in this fast-moving debate, and argues that the phenomenal aspects of conscious experience are aspects that exist only in the directing of experience towards non-phenomenal objects, a theory that undermines reductive attempts to explain consciousness in terms of what is not conscious. His book will be of interest to a wide range of readers in the philosophy of mind and language, psychology and cognitive science.